Students’ Errors in the Use of Present Participle in Translating Simple Dialog at the Eleventh Grade of SMK Taruna Masmur Pekanbaru - veby aisyah putri irawan; M. Syafi'i (Indonesian Journal of Integrated English Language Teaching, 2021)
The research proposed a formulation of the problem: what kinds of errors were produced in the use of present participle in translating simple dialog by the students at the eleventh grade of SMK Taruna Masmur Pekanbaru. The objective of the research was to explain the kinds of students’ errors in the use of present participle in translating simple dialog at the eleventh grade students of SMK Taruna Masmur Pekanbaru. The research design is descriptive research. The population of this research was the eleventh grade students of SMK Taruna Masmur Pekanbaru in 2017/2018 academic year. It consisted of one class; the number of population was 14 students. The sample of this research was 14 students. The instrument of this research were test and documentation. The technique of analyzing data was quantitative analysis. Based on the data analysis, the researcher concluded that the percentage of all indicators were misformation (40 errors or 56.3%), omission (17 errors or 23.9%), addition (13 errors or 18.3%), and misordering (1 error or 1.4%). From the data above the most common errors produced by the eleventh grade students of SMK Taruna Masmur Pekanbaru was misformation consisting of 40 errors or 56.3%.